(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The use of ergonomic studies and the training of future teachers of computer science, the factors for the effective use of computer programs in the study of pedagogy with the aim of convenient presentation of information using information technologies are highlighted. The issues of ensuring the work of a computer and its users with high motivation and minimal fatigue, the creation of optimal working conditions in terms of ergonomic design of human-computer interaction are considered.